2021
DOI: 10.1007/s00018-021-03999-0
|View full text |Cite
|
Sign up to set email alerts
|

Lipin-1-derived diacylglycerol activates intracellular TRPC3 which is critical for inflammatory signaling

Abstract: Exposure to Gram-negative bacterial LPS exacerbates host immune responses and may lead to sepsis, a life-threatening condition. Despite its high mortality and morbidity, no drugs specifically directed to treating sepsis are currently available. Using human cell genetic depletion, pharmacological inhibition, live-cell microscopy and organelle-targeted molecular sensors we present evidence that the channel TRPC3 is activated intracellularly during macrophage exposure to LPS and is essential for Ca2+ release from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…As cell membrane receptors, TRP ion channels can be regulated by a diverse range of physical stimuli and chemical agents as well as endogenous ligands. Many of these factors coincide with inflammatory elements [ 12 , 20 , 78 , 83 , 93 ]. It has been suggested that there are an abundance of intervention options available at this juncture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As cell membrane receptors, TRP ion channels can be regulated by a diverse range of physical stimuli and chemical agents as well as endogenous ligands. Many of these factors coincide with inflammatory elements [ 12 , 20 , 78 , 83 , 93 ]. It has been suggested that there are an abundance of intervention options available at this juncture.…”
Section: Discussionmentioning
confidence: 99%
“…Upon lipopolysaccharide (LPS) stimulation, M2 macrophages have elevated expression of TRPC1 that supersedes that of Orai1 in these cells [ 19 ]. TRPC3 has been identified as a novel effector for LPS-triggered Ca 2+ signaling in primitive macrophages [ 20 ]. One study indicates that the expression of TRPC5 negatively regulates the transformation of macrophages into the M1 phenotype by inhibiting their polarization [ 21 ].…”
Section: Distribution Of Trp Ion Channels In Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that TRP not only exists in the cell membrane but also in intracellular organelles ( 37 ). In the process of LPS activation, lipoprotein Lipin-1 stimulated the enrichment of endoplasmic reticulum DAG, the activation of endoplasmic reticulum TRPC3 channel, the release of ER calcium, the increase of Ca2+, the activation of NF-κB, and the upregulation of cytokines ( 38 ). Phagocytosis of immune cell function is closely related to TRPML channels ( 39 ).…”
Section: Trps Participate In the Regulation Of Macrophage Activation ...mentioning
confidence: 99%